2018
DOI: 10.5935/2595-0118.20180043
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of remifentanil versus dexmedetomidine in the incidence of pain in a post-anesthesia care unit after bariatric surgery

Abstract: BACKGROUND AND OBJECTIVES: Compare anesthesia techniques with sufentanil and intraoperative infusion of remifentanil or dexmedetomidine, and to then analyze their associations with the incidence of pain and other complications in the post-anesthesia care unit. METHODS: A retrospective analytical observational study conducted in a reference center for bariatric surgery in São Paulo, São Paulo State, Brazil. Patients (n=120) included in the study were randomly selected using this site's anesthesia records for ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Although not statistically relevant between the two surgical procedures, pain in this study was found more prevalent in patients undergoing the Bypass procedure in the first hours after surgery. A similar percentage was found in another study 42 , with the incidence of pain in the Post Anesthetic Recovery Room (PACU) being 52.5% (n = 63); 36.11% reported severe pain (defined as a score of 8 to 10 on the numeric scale). The incidence of postoperative pain after bariatric surgery in patients undergoing general anesthesia is a factor to be considered when choosing intraoperative anesthetics 42 .…”
Section: ■ Discussionsupporting
confidence: 83%
“…Although not statistically relevant between the two surgical procedures, pain in this study was found more prevalent in patients undergoing the Bypass procedure in the first hours after surgery. A similar percentage was found in another study 42 , with the incidence of pain in the Post Anesthetic Recovery Room (PACU) being 52.5% (n = 63); 36.11% reported severe pain (defined as a score of 8 to 10 on the numeric scale). The incidence of postoperative pain after bariatric surgery in patients undergoing general anesthesia is a factor to be considered when choosing intraoperative anesthetics 42 .…”
Section: ■ Discussionsupporting
confidence: 83%
“…In this sense, the half-life of the anesthetics used may be directly related to an anesthesia time of fewer than 100 min, as some studies have shown 18 , while in the present study, the average was superior to 150 min in both groups. Nevertheless, the more intense postoperative pain in the group submitted to the sleeve in the first hours after surgery may be intrinsically related to the anesthetics used intraoperatively, as observed in another study 21 , with the choice of anesthetic drugs being a factor that should be taken into account during the intraoperative period of patients undergoing bariatric surgery.…”
Section: Discussionmentioning
confidence: 86%